Doing qualitative research - Silverman, David (London Sage Publications, 2005)
David Silverman's seminal Doing Qualitative Research can justifiably claim to be `the supervisor in your pocket' for all PhD and Masters students embarking on their own qualitative research project.This hugely popular textbook has been fully revised and updated and is one of the few books available that can claim to be essential reading for anyone planning their own research project.Written in a lively, accessible style, this step-by-step guide provides answers to all the questions students ask when beginning their first research project. Silverman demonstrates how to learn the craft of qualitative research by applying knowledge about different methods to actual data. He provides practical advice on key issues, such as: defining `originality' and narrowing down a topic; keeping a research diary and writing a research report; and presenting research to different audiences.